Inhibition of Notch activity promotes pancreatic cytokeratin 5-positive cell differentiation to beta cells and improves glucose homeostasis following acute pancreatitis - Xiaoyi Zhang; Jing Tao; Jia Yu; Ning Hu; Xuanzhe Zhang; Guirong Wang; Jiarui Feng; Xingcheng Xiong; Man Li; Dongqi Chai; Hanjun Li; Yuping Rong; et al. (Cell Death and Disease, 2021)
Abstract Some individuals develop prediabetes and/or diabetes following acute pancreatitis (AP). AP-induced beta-cell injury and the limited regenerative capacity of beta cells might account for pancreatic endocrine insufficiency. Previously, we found that only a few pancreatic cytokeratin 5 positive (Krt5+) cells differentiated into beta cells in the murine AP model, which was insufficient to maintain glucose homeostasis. Notch signaling determines pancreatic progenitor differentiation in pancreas development. This study aimed to examine whether Notch signaling inhibition could promote pancreatic Krt5+ cell differentiation into beta cells and improve glucose homeostasis following AP. Pancreatic tissues from patients with acute necrotizing pancreatitis (ANP) were used to evaluate beta-cell injury, Krt5+ cell activation and differentiation, and Notch activity. The murine AP model was induced by cerulein, and the effect of Notch inhibition on Krt5+ cell differentiation was evaluated both in vivo and in vitro. The results demonstrated beta-cell loss in ANP patients and AP mice. Krt5+ cells were activated in ANP pancreases along with persistently elevated Notch activity, which resulted in the formation of massive duct-like structures. AP mice that received Notch inhibitor showed that impaired glucose tolerance was reversed 7 and 15 days following AP, and increased numbers of newborn small islets due to increased differentiation of Krt5+ cells to beta cells to some extent. In addition, Krt5+ cells isolated from AP mice showed increased differentiation to beta cells by Notch inhibition. Collectively, these findings suggest that beta-cell loss contributes to pancreatic endocrine insufficiency following AP, and inhibition of Notch activity promotes pancreatic Krt5+ cell differentiation to beta cells and improves glucose homeostasis. The findings from this study may shed light on the potential treatment of prediabetes/diabetes following AP.